UMPSA Academics bring English and AI Learning to secondary school students in CSR Outreach at SMATAF - Noor Raha, Mohd Radzuan; Abdullah Adnan, Mohamed; Ezihaslinda, Ngah; Muhammad musab, Azmat Ali (UMPSA, 2025)
PEKAN, 16 July 2025 – The Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), made a significant impact on the English language learning experience of secondary school students through a dynamic and technology-integrated Corporate Social Responsibility (CSR) programme held at Sekolah Menengah Agama Tun Abdul Razak (SMATAF).